Can an educational intervention in the context of inpatient pulmonary rehabilitation improve asthma self-management at work? A study protocol of a randomized controlled trial - Julia Salandi; Markus C. Hayden; Katherina Heinrichs; Matthias Limbach; Konrad Schultz; Gabriele Schwarzl; Wolfgang Neumeister; Adrian Loerbroks (BMC Pulmonary Medicine, 2024)
Abstract Background Asthma self-management (e.g., trigger avoidance or correct medication use) is a cornerstone of therapy. Its successful implementation in everyday working life is determined by psychosocial working conditions, in particular by support from superiors and colleagues and the job decision latitude (i.e., when and how to carry out which tasks). To empower individuals with asthma to modify their working conditions, employees need to use certain communication skills and acquire specific knowledge. Both could be taught as part of patient education during pulmonary rehabilitation. Therefore, the aim of the planned study is the development and multicentre implementation of an education module for individuals with asthma during their rehabilitation and to generate evidence on its effectiveness. Methods Participants (n ≥ 180) will be recruited, randomized into an intervention and a control group, trained and surveyed in two rehabilitation clinics. The intervention group will receive the supplementary patient education module “Asthma and Work” while the control group will participate in a program on " Eating behaviour” (both 2 × 50 min). The effectiveness of the intervention will be examined based on pre-post measurements (T1 and T2) and a 3-month follow-up (T3). We will consider behavioural intention (T2) and asthma self-management at work (T3) as primary outcomes. Secondary outcomes will include self-management-related knowledge, self-efficacy, number of sick days, number of exacerbations, asthma control (Asthma Control Test), asthma-related quality of life (Marks Asthma Quality of Life Questionnaire), and subjective employment prognosis (Brief Scale Measuring the Subjective Prognosis of Gainful Employment). The pre-post comparisons are to be evaluated using univariate analyses of covariance. Discussion Improving asthma self-management at work could increase the work ability and social participation of employees with asthma. This could reduce costs, e.g. in terms of asthma-related sick leave. Trial registration German Clinical Trials Register (ID: DRKS00031843)